An Electron Microscopic Study of the Ductuli Efferentes and Rete Testis of the Guinea Pig - Ladman, Aaron J. (The Rockefeller University Press, 1958)
The ductuli efferentes and rete testis of the guinea pig were isolated by micro dissection, fixed in cold buffered osmium tetroxide, and sectioned for examination with the light and electron microscopes. Proximal and distal segments of the ductuli efferentes were identified and their respective cytological organizations characterized. The cytological components of the rete testis are briefly described and figured. Non-ciliated and ciliated cells are found in both segments of the ductuli efferentes. The non-ciliated cells have a microvillous border, mitochondria, a Golgi complex, an ubiquitous endoplasmic reticulum, and numerous cytoplasmic vacuoles. The ciliated cells contain more mitochondria, an endoplasmic reticulum with a relatively sparse distribution, and few, if any, cytoplasmic vacuoles. A regional difference exists in proximal and distal segments based on the distribution, size, number, and electron opacity of the cytoplasmic vacuoles. Attention was paid to the disposition of the endoplasmic reticulum and its relation to the system of cytoplasmic vacuoles. These findings are interpreted as suggesting that the continuity of the vacuolar system with elements of the endoplasmic reticulum represents a pathway for transfer of large quantities of fluid, an activity which has long been ascribed to the epithelium of the ductuli efferentes. Periductular capillaries possess pore-like apertures in their endothelia similar to those in other tissues known to engage in fluid transfer.